Correlation of Serum Sodium with Severity of Hepatic Encephalopathy - Arshad, Muhammad; Zeb, Shah; Tauseef, Muhammad Atif; Ullah, Najeeb (Journal of Gandhara Medical and Dental Science, 2016)
INTRODUCTION Hepatic encephalopathy (HE) is neuropsychiatric syndrome for which symptoms, manifested on a continuum, is deterioration in mental status, with psychomotor dysfunction, impaired memory, increase reaction time, poor concentration, disorientation, and in severe form coma and may develop at an annual rate of 8% in cirrhotic patients in Far Eastern studies. Fluctuation in serum sodium level is a frequent complication of advanced cirrhosis related to impairment in the renal capacity to eliminate solute-free water that causes retention of water that is disproportionate to the retention of sodium, thus causing a reduction in serum sodium concentration and hypo-osmolality. Hyponatremia is a common finding in patients with decompensated cirrhosis due to an abnormal regulation of body fluid homeostasis. OBJECTIVE To determine the correlation of serum sodium with severity of hepatic encephalopathy MATERIAL AND METHODS This study was conducted at Naseer Teaching Hospital Peshawar. Duration of the study was 01 year and the study design was cross sectional (Correlation) study in which a total of 408 patients were observed by using – 0.1411 of correlation coefficient between serum sodium and hepatic encephalopathy 95% confidence level and 80% power of test. More over non probability consecutive sampling was used for sample collection. RESULTS In this study mean age was 65 years with SD ± 0.315. Sixty two percent patients were male and 38% patients were female. Mean serum sodium level was 123 meq/L with SD ± 0.21. Five percent patients had severity of grade I, 39% patients had severity of grade II, 48% patients had severity of grade III and 8% patients had severity of grade IV. Correlation of severity of hepatic encephalopathy with serum sodium level was analyzed as all the 20 patients with severity of grade I had serum sodium level ranged 131-133 meq/L. All the 159 patients with severity of grade II had serum sodium level ranged 126-130 meq/L. In 196 patients with severity of grade III, 45 patients had serum sodium level ranged 126-130 meq/L while 151 patients had serum sodium level ranged 120-125 meq/L where as all the 33 patients with severity of grade IV had serum sodium level ranged 120-125 meq/L. CONCLUSION Hyponatremia was a common feature in patients with cirrhosis and its severity increased with the severity of liver disease. The existence of serum sodium concentration < 135 mmol/L was associated with greater frequency of hepatic encephalopathy. It was also noticed that more severe the hyponatremia, greater will be the grade of hepatic encephalopathy. Close monitoring of serum sodium concentration should be performed in patients with cirrhosis in order to prevent the rapid development of cirrhosis related complications.